Os métodos Viewpoints e Suzuki em interface à composição visual - Luciana do Espirito Santo Brandao (2018)
The present master thesis works with the Viewpoints and Suzuki training methods examined from a historical perspective and were exposed to their own form of dialogue. The cut is made between theatrical trainings and Fine Arts and is from the book Point, Line under Plan by Wassily Kandinsky. Thusfore, a reflection on the concepts: scenic presence, movement and scenic / theatrical space in relation to the notion of Point, Line and Plane. From the comparative analyzes, suggesting new fields of perception about the exercise of actor / actress